Relationship between Human Perceptional Dimensions with Factors of Identity in Architecture - sajad damyar (مسکن و محیط روستا, 2014)
Identity has been at the center of architectural discourse from World War II. But its multi-dimensional nature which goes back to its relevance to many fields of humanities (sociology, psychology, urbanism etc.) made its literature vague to some extent. To make a clarification of meaning of identity due to its abstract relation to built environment is the main purpose of this research. The method of confronting the problem is analyzed by using Geddes’s thinking machine where one of the four possible ways in it selected for this study. Here the priority is placed on concept of Identity and Architectural Identity is seen as a subdivision of it. Before concentrating on absolute concept of architectural identity, a brief discussion of various kinds of identity in literature of architectural theory is considered where four main type is identified: personal or group identity via architectural form, socio-cultural identity interpreted via built environment, human identity for himself pursued via architecture and architectural absolute identity (as the one that no other thing than architecture itself is under consideration).  If we define identity as a kind of recognition which arises from human experiment with built space or unity of mental expectation with perceptional content of this experiment, then it would be a natural strategy to pursue the subject via human perceptional dimensions. These dimensions upon their place in the spectrum of material-spiritual perception can be proposed in four categories: 1. Physical or bodily dimension 2. Mental dimension 3. Social dimension  4. Spiritual dimension. These kinds of perceptions are in turn subdivided in two main categories due to their source of stimulation: natural environment or man-made environment. There is a third and important factor for analyzing these four types of recognition that must be taken into account: what kind of recorded content of the brain is referred to. At least four kinds of them can be seen due to the duration of the recorded humane experiment: 1. Immediate perception 2. Life-long experiment 3. Inherited image from previous generations (archetypical) and 4.timeless experiment of human-being upon these three factors, a cubical model of 32 separate positions each of which is representative of a different dimension of architectural identity as it relates to human experiment. It is supposed that any characteristic of human perception which can be related to absolute identity of architecture has a certain location in this model, so the model is holistic in containing all possibilities but not in proving any claim about existence or non-existence of any kind of humane experiment. For searching the potential of the model to make this holistic view, a real example of vernacular architecture of Ilam (a south-western province of Iran) is explored from point of view of identity of built environment for vernacular people, both dwellers of such an environment and non-dwellers. This study which is presented in a table, shows the potential of model not only for having  a systematic analysis of identity aspects of an architecture but also makes it evident that via such a model we can guess some new aspects of identity of that case which have not ever been considered.